IDENTIFIKASI DAN ANALISIS KOMPLIKASI MAKROVASKULER DAN MIKROVASKULER PADA PASIEN DIABETES MELLITUS - Nauli, Fathra Annis; YUHELMA, YUHELMA '; Hasneli, Yesi ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2015)
Abstract The purpose of this research was to identify and analyse macrovascular and microvascular complications among with diabetes mellitus patients in Arifin Achmad Hospital Pekanbaru. The samples was 72 patients with diabetes mellitus sampling used purposive sampling method. The research instrument used the observation sheet. The analysis used univariate and OR. Some respondent on late adulthood experienced macrovascular complications (44.6%) and microvascular (80%) with the OR 3.467, which means late adulthood are at risk for complications 3.467 times larger than early adulthood. OR for long suffered from DM category obtained that some respondents who long suffered from diabetes <5 years had macrovascular complications (64.3%) and microvascular (45%) and the respondents with long suffered from DM>5 years had macrovascular complications (35.7%) and microvascular (55%) with the odds ratio 2.200, which means long suffering from DM <5 years are at risk for macrovascular and microvascular complications 2,200 times more than the respondents with long suffered from DM>5 years. The results of this reserach can provide information for patients in improving the quality of life and prevent complications caused by diabetes. Keywords: complications, diabetes mellitus, makrovaskuler, microvascular. Bibliography: 49 (2003-2013)